1995
DOI: 10.1007/bf01218360
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of cellular radiosensitivity between different localizations of head and neck squamous-cell carcinoma

Abstract: The prognosis of carcinomas arising from various sites in the head and neck varies even when the stage of the disease is taken into consideration, e.g. laryngeal carcinoma has a more favourable prognosis compared to oral-cavity malignancies. The purpose of this study was to evaluate intrinsic cellular radiosensitivity as one possible explanation for the observed differences in the survival rates of different anatomical groups. The radiation survival curves were determined for well characterized cell lines deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 13 publications
2
23
0
Order By: Relevance
“…stage, nodal status and patient age, and this confirms the findings of others (Brock et al, 1992;Girinsky et al, 1993Girinsky et al, , 1994. This study also confirmed the finding that there are no significant differences in mean radiosensitivity for tumours of different sites within the head and neck region (Girinsky et al, 1993;Pekkola-Heino et al, 1995). The latter observation, however, is in contrast to a report by Brock et al (1992), who found that oral cavity tumours were more radioresistant than carcinomas of the larynx, an observation that is consistent with clinical observations (Corv6 et al, 1994).…”
Section: Discussionsupporting
confidence: 91%
“…stage, nodal status and patient age, and this confirms the findings of others (Brock et al, 1992;Girinsky et al, 1993Girinsky et al, , 1994. This study also confirmed the finding that there are no significant differences in mean radiosensitivity for tumours of different sites within the head and neck region (Girinsky et al, 1993;Pekkola-Heino et al, 1995). The latter observation, however, is in contrast to a report by Brock et al (1992), who found that oral cavity tumours were more radioresistant than carcinomas of the larynx, an observation that is consistent with clinical observations (Corv6 et al, 1994).…”
Section: Discussionsupporting
confidence: 91%
“…ICS is reported in terms of the surviving fraction of cells, and varied from 0.00 to 1.00, with a median of 0.52 in the investigated cell lines (Table I). The intrinsic radiosensitivity (IR) of these cell lines was previously determined (19). The IR was given in terms of mean inactivation dose (AUC = area under curve), and varied between 1.4 and 2.6, with a median of 2.0 (Table I).…”
Section: Resultsmentioning
confidence: 99%
“…The 96-well plate clonogenic assay was performed as previously described (19,20). In brief, the cells were harvested with trypsin/ EDTA, counted, and diluted to form a stock solution.…”
Section: Assessment Of Intrinsic Radiosensitivity (Ir)mentioning
confidence: 99%
“…The cells were grown to midlogarithmic phase and fed with fresh medium 24 h before the experiments. The 96-well plate clonogenic assay was performed as previously described (18,20,21). In brief, the cells were harvested with trypsin/EDTA, counted and diluted to a stock solution.…”
Section: Methodsmentioning
confidence: 99%
“…Nine recently established HNSCC cell lines were selected for this study to represent different parts of the in vitro radiosensitivity spectrum (Table I). The average intrinsic radiosensitivity (IR), measured with a 96-well clonogenic assay plate in a large panel of HNSCC cell lines was 1.9 for head and neck cancer of all sites (18). The cells were cultured in Dulbecco's modified Eagle's medium, supplemented with 2 mM glutamine, 1% non-essential amino acids, 100 IU/ml penicillin-G, 50 μg/ml streptomycin and 10% fetal bovine serum (all from Gibco, Paisly, UK).…”
Section: Methodsmentioning
confidence: 99%